Ferroelectricity in yttrium-doped hafnium oxide - Müller, Johannes; Schröder, Uwe Paul; Böschke, Tim S.; Müller, I.; Böttger, U.; Wilde, Lutz; Sundqvist, Jonas; Lemberger, Martin; Kücher, Peter; Mikolajick, Thomas; Frey, Lothar (Journal of Applied Physics, 2011)
structural and electrical evidence for a ferroelectric phase in yttrium doped hafnium oxide thin films is presented. A doping series ranging from 2.3 to 12.3 mol YO 1.5 in HfO 2 was deposited by a thermal atomic layer deposition process. Grazing incidence X-ray diffraction of the 10 nm thick films revealed an orthorhombic phase close to the stability region of the cubic phase. The potential ferroelectricity of this orthorhombic phase was confirmed by polarization hysteresis measurements on titanium nitride based metal-insulator-metal capacitors. For 5.2 mol YO 1.5 admixture the remanent polarization peaked at 24 Ccm 2 with a coercive field of about 1.2 MVcm. Considering the availability of conformal deposition processes and CMOS-compatibility, ferroelectric Y:HfO 2 implies high scaling potential for future, ferroelectric memories. © 2011 American Institute of Physics.
UnivIS-Import:2017-07-10:Pub.2011.tech.IE.LEB.roelec